“DUTA BACA MAKEDONIA” UNTUK MENINGKATKAN KEMAMPUAN INTELEKTUAL, MORAL DAN SPIRITUAL SISWA KELAS 3-6 DI DUSUN MUNGGU LUMUT, KALIMANTAN BARAT - Siregar, Esron; Mangantibe, Julius; Sarumaha, Simeri Hati; Laoli, Arosokhi; Netsen (Jurnal PKM Setiadharma, 2024)
This research is motivated by the fact that third to sixth-grade elementary school students in Munggu Lumut village struggle with illiteracy and numeracy, coupled with low spiritual quality manifested in behaviors such as theft, lying, and mockery. The Duta Baca Makedonias program emerges as a potential educational partner for Munggu Lumut village and local schools, aiming to empower students with reading, writing, and arithmetic skills while fostering a Christian character rooted in the Bible. Through intellectual, moral, and spiritual education, the aspiration is to cultivate a generation capable of contributing to the progress of the nation and the state. Key educational activities, including tutoring sessions in reading, writing, and arithmetic, as well as spiritual guidance through Bible-based sermons, prayers, and Christian counseling, are integral to achieving these objectives. The research employs a qualitative methodology with a field case study, utilizing observation, interviews, and documentation as data collection techniques. The analysis reveals that the Duta Baca Makedonias  program has successfully enabled third to sixth-grade students in Munggu Lumut village to acquire essential literacy and numeracy skills, as well as to abandon undesirable behaviors